Keanekaragaman Species dan Struktur Komunitas Serangga di Area Reklamasi Bekas Tambang Batubara di Kabupaten Muaro Jambi, Provinsi Jambi - Ratna Rubiana; Rima Purnamayani; Araz Meilin (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Rubiana et al, 2018. Species Diversity and Community Structure of Insect in the Former Area of Coal Mining Reclamation in Muaro Jambi District, Jambi Province. JLSO 7(1):37-42.Â Recovery of land and ecosystems in the form of reclamation is expected to restore lost biodiversity. The success of reclamation can be seen from the recovery of ecosystems and biodiversity in it. However, the study of biodiversity on reclaimed land in Indonesia is still limited to vegetation and has not seen groups of animals especially insects. Insects have a very important functional role in the ecosystem, therefore they can be used as objects of diversity studies in the reclamation area. This study aimed to study the diversity and functional role of insects in the reclamation area. The study was conducted in the reclamation area of a former coal mine in Muaro Jambi Regency. The study area consisted of two different revegetation ages and two different plants. The method of insect collection is by installing pitfall traps with five replications for 2 x 24 hours. The insects were collected from the pitfall trap then identified to the morphospecies level. The results showed that most of the Coleoptera, Diptera, Hymenoptera and Othroptera insects were found in the reclamation area. Insect diversity is influenced by the age of reclamation. One year of reclamation had a lower species than insect age of two years. Based on the results of the analysis show that the composition of insect species showed differences at different reclamation ages. The older the age of reclamation, the composition of insect species tended to resemble the composition of insect species in the forest.